CREATIVE TOURISM AND SUSTAINABLE DEVELOPMENT OF CITIES: A REVIEW OF THE LITERATURE - Costa, Vânia; Pereira, Raquel (Brazilian Creative Industries Journal, 2022)
The tourism sector has experienced unparalleled challenges, particularly with the Covid-19 pandemic. These challenges are an opportunity to focus on developing coordinated strategies and actions to promote sustainable and socially responsible tourism and thus accelerate the achievement of the UN Sustainable Development Goals by 2030. This research aims to identify and analyze literature that specifically addresses creative tourism as a model for sustainable development of tourism in cities. It aims to fill a gap in the knowledge of the field, as no reviews with this focus have yet been undertaken. The Web of Science (WoS) database was used to extract the publications and VOSviewer software was used to represent the analyzed data. The study analyses publications with the keywords “creative tourism” and “sustainability” and “cities” in titles, keywords and abstracts in the WOS database. The analysis identified publications representing a new line of research that has been evolving, identifying the authors, the countries, the journals, the study areas, and the publications that stand out concerning the analysis of this specific topic. The studies referring to the theme present an approach of conceptualisation and proposal of models and development of creative tourism and promote the planning and management of the territories attending to a creative and sustainable perspective. The main contribution of this research is the analysis of the corresponding literature aiming at rethinking and revitalising the tourism sector and territories in an integrated perspective and sustainable management in the planning processes of tourism destinations.